Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1177/0020764006067234
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Who Bully Students: A Hidden Trauma

Abstract: Objective: The study examined teachers' perceptions of bullying by other teachers to see what causes and characteristics were attributed to such bullying teachers, and how often teachers were themselves bullied by students. Method: 116 teachers from seven elementary schools completed an anonymous questionnaire reflecting their feelings and perceptions about theirown experiences of bullying, and how they perceive colleagues over the years. Results: Resultsconfirmed that teachers who experienced bullying themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
1
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 11 publications
4
66
1
11
Order By: Relevance
“…Newman, Frey, and Jones (2010) suggested that the influence of teachers' own experience with bullying and its impact on how they may experience bullying among students warrant investigation. Twemlow, Fonagy, Sacco, and Brethour (2006) found that teachers were more likely to both bully students and be aggressed by students if they had been bullied in their own childhood. Thus, it may be that teachers' early experience with bullying influences their cognitive and affective responses to bullying incidents, which then in turn impact how they respond to these incidents.…”
Section: Individual Teacher Characteristicsmentioning
confidence: 99%
“…Newman, Frey, and Jones (2010) suggested that the influence of teachers' own experience with bullying and its impact on how they may experience bullying among students warrant investigation. Twemlow, Fonagy, Sacco, and Brethour (2006) found that teachers were more likely to both bully students and be aggressed by students if they had been bullied in their own childhood. Thus, it may be that teachers' early experience with bullying influences their cognitive and affective responses to bullying incidents, which then in turn impact how they respond to these incidents.…”
Section: Individual Teacher Characteristicsmentioning
confidence: 99%
“…Research has mostly studied bullying at the peer group level, emphasizing its role in influencing the current and future behaviors of the perpetrators, victims, and witnesses (Salmivalli et al, 1996;Salmivalli, 2010;Boulton et al, 2017). However, while reactions from peers certainly affect how students may become involved in and cope with these events (Saarento et al, 2015), other facts are just as important.Recent research has stressed the role of teachers in recognizing episodes of bullying and identifying their actors, as well as in preventing and intervening on them (DeOrnellas and Spurgin, 2017 reinforces or inhibits the various possible behaviors on the part of the bullies, the victims, and the bystanders (Craig et al, 2011), and in general affects how pupils perceive and react to bullying (Gini, 2005;Twemlow et al, 2006;Bjereld et al, 2017). Indeed, there is evidence showing that students who perceive their teachers as disapproving of bullying are less likely to bully others; conversely, bullying is more common when students feel that their teachers tolerate it (Saarento et al, 2013).…”
mentioning
confidence: 99%
“…Recent research has stressed the role of teachers in recognizing episodes of bullying and identifying their actors, as well as in preventing and intervening on them (DeOrnellas and Spurgin, 2017 reinforces or inhibits the various possible behaviors on the part of the bullies, the victims, and the bystanders (Craig et al, 2011), and in general affects how pupils perceive and react to bullying (Gini, 2005;Twemlow et al, 2006;Bjereld et al, 2017). Indeed, there is evidence showing that students who perceive their teachers as disapproving of bullying are less likely to bully others; conversely, bullying is more common when students feel that their teachers tolerate it (Saarento et al, 2013).…”
mentioning
confidence: 99%
“…Twemlow et al (2006) Oldenburg et al (2015), as salas de aulas de professores que relatam terem sido agressores, quando estudantes, apresentam maior frequência de agressões, em comparação com as salas de aula de professores que não foram agressores. Isto, talvez, se deva ao fato de esses professores não considerarem as agressões praticadas em sala de aula como um problema.…”
Section: Crenças Dos Professores Sobre Bullyingunclassified